Orchialgia After Living Donor Nephrectomy: An Underreported Entity. Issue 11 (24th October 2022) - Schoephoerster, Jamee; Matas, Arthur; Jackson, Scott; Pruett, Timothy L.; Finger, Erik; Kandaswamy, Raja; Dunn, Ty; Kirchner, Varvara; Anderson, J. Kyle; Humphreville, Vanessa
Abstract : Background: Laparoscopic donor nephrectomy (LDN) offers advantages to the donor. The reported incidence of testicular pain after LDN varies in the literature ranging from 3% to 55%. Methods: A survey was sent to 322 male LDN patients who donated from February 5, 2009, to February 5, 2019. The survey assessed if the donor had testicular pain or saw an additional medical professional after donation. Results: Of the 322 surveyed, 147 (46%) responses were received. Of those who had a left nephrectomy, 39% had testicular pain; 23.8% of those patients had testicular swelling in addition. Of those who had pain, laterality of kidney donated did not impact if the patient had pain, pain onset, pain level, or pain duration. Of those who donated their right kidney, 35% had testicular pain, and 16.7% of those patients reported testicular swelling in addition. Twenty-seven symptomatic patients sought additional medical care for the testicular symptoms postdonation. Seven (25%) had hydroceles, 2 (7%) had testicular cysts, 1 had a urinary tract infection, and 16 (59%) had reassurance or no additional procedures provided. Conclusions: Our results suggest that orchialgia is not as uncommon as previously thought and may be one of the most common minor complications experienced by male donors.